2015
DOI: 10.1111/bjh.13859
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ and intra‐patient clonal and subclonal heterogeneity of chronic lymphocytic leukaemia: evidences from circulating and lymph nodal compartments

Abstract: Summary Whole exome sequencing and copy number aberration (CNA) analysis was performed on cells taken from peripheral blood (PB) and lymph nodes (LN) of patients with chronic lymphocytic leukaemia (CLL). Of 64 non-silent somatic mutations, 54 (84.4%) were clonal in both compartments, 3 (4.7%) were PB-specific and 7 (10.9%) were LN-specific. Most of the LN- or PB-specific mutations were subclonal in the other corresponding compartment (variant frequency 0.5-5.3%). Of 41 CNAs, 27 (65.8%) were shared by both comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…lymph node and peripheral blood) and showed that mutations in the lymph nodes expand in the peripheral blood at relapse following positive selection by therapy (Schuh et al , ; Del Giudice et al , ; Rose‐Zerilli et al , ). Using NGS and copy number alteration/aberration analysis of leukaemic cells isolated simultaneously from peripheral blood and lymph node of nine CLL patients, Del Giudice et al () identified specific subclonal mutations in each compartment and cases with clonal driver aberrations within lymph nodes ( SF3B1 mutation, BIRC3 deletion, del8p and gain 2p) that were only detected in the blood as small circulating subclones. Several groups have reported on acquired ibrutinib resistance and BTK and PLCG2 mutations in patients with CLL who progressed on ibrutinib therapy (Woyach et al , ; Burger et al , ; Ahn et al , ).…”
Section: Clonal Evolutionmentioning
confidence: 99%
“…lymph node and peripheral blood) and showed that mutations in the lymph nodes expand in the peripheral blood at relapse following positive selection by therapy (Schuh et al , ; Del Giudice et al , ; Rose‐Zerilli et al , ). Using NGS and copy number alteration/aberration analysis of leukaemic cells isolated simultaneously from peripheral blood and lymph node of nine CLL patients, Del Giudice et al () identified specific subclonal mutations in each compartment and cases with clonal driver aberrations within lymph nodes ( SF3B1 mutation, BIRC3 deletion, del8p and gain 2p) that were only detected in the blood as small circulating subclones. Several groups have reported on acquired ibrutinib resistance and BTK and PLCG2 mutations in patients with CLL who progressed on ibrutinib therapy (Woyach et al , ; Burger et al , ; Ahn et al , ).…”
Section: Clonal Evolutionmentioning
confidence: 99%
“…Taken together, the data reported by Del Giudice et al () confirmed that CLL is not a static entity, but rather a dynamic disease characterized by a heterogeneous subclonal architecture that changes over time and is influenced by selection pressures. Importantly, novel evidence is provided that highlights the importance of the LN TME/niche as the potential site of origin for dominant clones that emerge with disease evolution.…”
mentioning
confidence: 58%
“…In this issue of the British Journal of Haematology , Del Giudice et al () have applied for the first time NGS and Copy Number Aberration (CNA) analysis to nine CLL patients whose leukaemic cells were extracted simultaneously from peripheral blood (PB) and lymph node tissue (LN), to examine disease genomic architecture at the clonal and subclonal level in these immune system compartments. As expected, the analysis revealed a high degree of intra‐ and inter‐patient heterogeneity, with 6 of 9 cases (66·7%) showing a different clonal architecture of mutations and/or CNAs between PB and LN compartments.…”
mentioning
confidence: 99%
“…We have previously reported the presence of BIRC3 mutations in 27% of 11q− chemo‐refractory CLL patients (Messina et al , ) and the clonal expansion in the peripheral blood at relapse of BIRC3 deletion derived from the lymph node (Del Giudice et al , ). Thus, BIRC3 lesions could have a role as a predictive marker in CLL treated with chemoimmunotherapy (Diop et al , ).…”
Section: Clinical and Biological Characteristics Of The 134 11q− Cll mentioning
confidence: 95%